(untitled) (Comprehensive Journal of Science, 2026)
This paper provides a comprehensive technical investigation into the frequency spectrum utilization of 5G New Radio (NR) and 5G-Advanced systems. As the demand for multi-gigabit throughput increases, the transition from Frequency Range 1 (FR1) to Frequency Range 2 (FR2) presents unique challenges in wave propagation and signal processing. This study analyses the mathematical foundations of Path Loss, the application of the Shannon-Hartley theorem to wideband channels, and the role of Massive MIMO in mitigating high-frequency attenuation.